Stirred tank bioreactor process for chikungunya vaccine candidate VEEV-ΔC-CHIKV - Tong Chang; ChengLin Deng; LiXia Xie; Yifan Zheng; Yanan Zhang; Jiawei Liu; ZhenFang Fu; Bo Zhang; Qi An; DaYong Tian (PLoS ONE, 2026)
Chikungunya virus (CHIKV), a mosquito-borne alphavirus with significant public health impact, has caused recurrent epidemics across Africa, Asia, and the Americas. Despite the recent approval of a live-attenuated vaccine (Chix), scalable manufacturing processes for CHIKV vaccines remain critical to meet global demand. In this context, we previously constructed a chimeric virus, VEEV-ΔC-CHIKV, by replacing the backbone of ΔC-CHIKV with that of the VEEV replicon while retaining the CHIKV antigenic glycoprotein (E3-E2-6K-E1). A series of experiments have demonstrated that the chimeric virus exhibits safety, stability, and immunogenicity, making it a promising candidate for a new attenuated live vaccine strain. Therefore, to further validate its viral properties and explore the potential for large-scale production, we developed an optimized bioreactor-based production process for VEEV-ΔC-CHIKV. Utilizing adherent Vero cells in mechanically stirred bioreactors, we systematically optimized key parameters, including carrier type selection, cell seeding density, human albumin supplementation, and nutrient modulation, to maximize viral titers while minimizing the accumulation of metabolic byproducts. Results indicated that Cytodex™ 1 microcarriers outperformed Fibra-Cel carriers, enabling 10 consecutive harvests with viral titers ≥ 10 5 PFU/mL (compared to 4 harvests for Fibra-Cel). When the initial cell density was 6.5 × 10 5 cells/mL, the total virus yield was 77% higher than at a cell density of 2.5 × 10 5 cells/mL. Adding 1.0% human albumin doubled total virus production compared to the addition of 0.5%. Nutrient modulation through the maintenance of glucose (>3 g/L) and glutamine (>0.5 g/L) in fed-batch systems enhanced peak titers to 10 6.4 PFU/mL, representing a 2.2-fold increase compared to non-fed controls. This study establishes a scalable and cost-effective bioreactor platform for the production of the CHIKV vaccine, highlighting the critical interplay between nutrient optimization and viral yield enhancement, while emphasizing the advantages of automated process control in bioreactors to facilitate large-scale, high-yield viral production.